Microcap M&A: An Exploratory Study - Adam Steen; Keith Turpie; Gee Wan Ng (Australasian Accounting, Business and Finance Journal, 2014)
A substantial body of accounting and finance literature has been devoted to the study of Mergers and Acquisitions (M&As) dominated by discussions relating to the gains and losses that accrue from transactions involving large public companies. This paper makes a unique contribution to the literature by investigating the M&A experience of microcap businesses. Transactions involving microcap M&A are substantially different to those involving large companies on a number of dimensions. This paper explores the determinants of microcap M&A success and pitfalls and problems from an integration perspective. Due to the paucity of research in the area an exploratory research design is employed, conducting interviews with five CEOs of companies that had each managed multiple transactions. We find microcap M&As are successful when measured against identified goals but generally take longer and cost more than expected. Further, culture and communication are key issues in determining success/failure. We also find the in-house management of integration aspects is problematic for these businesses and suggest this warrants further study.
Keywords: Merger; Acquisition; Integration; Microcap